Extraction of protein from moringa oleifera leaves for facial mask production - Shahidah Irsalina Mustafa Kamal Israk; Norliza Abd Rahman; Mohd Nazri Fuad; Jarinah Mohd Alia (Penerbit Universiti Kebangsaan Malaysia, 2021)
The use of facial mask is spreading wide all around the world due to its health benefits in skincare. There are many cases of cosmetic or beauty products containing ingredients that are not suitable for the skin where the pH reading increases or decreases due to either too acidic or alkaline. This research is conducted in order to determine the protein content in Moringa oleifera leaves and skincare product for the production of halal-certified facial mask. The extraction and determination of protein content are conducted using salting-out method with ammonium sulfate and by Bradford assay method. The extraction of protein from the leaves is done by using different weight of leaves, whereby the results for all samples are compared. This research is also conducted to produce a facial mask from the extracted protein from Moringa oleifera leaves using a suitable and the best formulation. Randomly selected respondents were asked to fill out a questionnaire to assist in this study. The survey was conducted using the ‘Google Form’ application as a platform. The formulated facial mask and the facial mask available in the market are then taken for a few parameter analyses. Final results showed the average protein content percentage in Moringa oleifera leaves is 33.33% and 16.67% in facial mask. The pH value for Moringa oleifera leaves is recorded to be in the range of pH 5.0- 6.0. The pH value for Moringa oleifera leaves is pH 5.01 and pH 5.29 for facial mask. A total of 45 respondents participated in the questionnaire analysis and 91.1% of them were women. A total of 68.9% were facial beauty masks users.